2003
DOI: 10.1196/annals.1304.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Harmane on Mononeuropathic Pain in Rats

Abstract: This study was designed to investigate the effect of the endogenous beta-carboline, harmane, on neuropathic pain produced by chronic constriction injury (CCI) of the sciatic nerve. Thermal allodynia evaluations were made preoperatively, postoperatively on the fifteenth day, and after harmane administration. Harmane (1, 2.5, 5, 10, or 20 mg/kg) was administered intraperitoneally for 5 days beginning from postoperative day 15. Treatment with harmane had a profound anti-allodynic effect in a dose-dependent manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Agmatine and harmane are the potent endogenous ligands that activate imidazoline I 1 and I 2 receptor. It is important to note that these agents themselves exhibit antinociceptive profile in neuropathic pain [68,69]. Interestingly, we found that pretreatment of these agents potentiated the antinociceptive effect of ethanol as well as nicotine.…”
Section: Discussionmentioning
confidence: 65%
“…Agmatine and harmane are the potent endogenous ligands that activate imidazoline I 1 and I 2 receptor. It is important to note that these agents themselves exhibit antinociceptive profile in neuropathic pain [68,69]. Interestingly, we found that pretreatment of these agents potentiated the antinociceptive effect of ethanol as well as nicotine.…”
Section: Discussionmentioning
confidence: 65%
“…On the other hand, H induced antidepressant and antianxiety effects in rats, as well as a vasorelaxant effect (19,20), and showed anti-HIV activity by inhibiting replication in H9 lymphocyte cells (21). Meanwhile, it was described that H may have beneficial effects on mononeuropathic pain in rats (22) and on naloxone-precipitated withdrawal syndrome in morphine-dependent rats (23). H also increased insulin secretion from isolated human islets of Langerhans (24).…”
Section: Introductionmentioning
confidence: 99%